Expired Epinephrine Maintains Chemical Concentration and Sterility. (4th July 2018) - Weir, William Bradley; Fred, Linda Y.; Pike, Matthew; Rubakhin, Stanislav S.; Ludwig, Tyler J.; Shar, Ashley M.; Zhu, Lingyang; Frederick, Ann; Uzoaru, Ike; Wang, Lin; Sweedler, Jonathan V.
Abstract: Objectives : Epinephrine shortages affect nearly all American emergency medical services (EMS) systems. Utilization of expired epinephrine could mitigate this situation in daily EMS operations. Concerns about using expired medications include sterility, potency, and potential harmful chemical decay byproducts. There are no cross-platform analyses of sterility and chemical purity of multiple samples of expired parenteral epinephrine. We hypothesized that epinephrine injections will remain sterile and will retain their active ingredient's content for more than 30 months past expiration.Methods : Six parenteral epinephrine prefilled syringes, 1 mg/10 mL, with an expiration date of January 1, 2012 had been stored in the climate controlled setting of a hospital inpatient pharmacy where they remained until they were taken for chemical or microbial analysis 30 months after expiration. An unexpired parenteral epinephrine prefilled syringe content was used as a control. Contents of three separate syringes with expired content from the same lot and one control underwent ultra-high pressure liquid chromatography-mass spectrometry (UHPLC-MS) and nuclear magnetic resonance (NMR) to determine epinephrine content and stability. In parallel, contents of another three expired epinephrine syringes were analyzed for sterility by plating on aerobic, anaerobic, and fungal media in a hospital microbiology laboratory. The aerobic plates were checked for growth in 3 days, the anaerobic in 5 days, and the fungal in 28 days.Results : UHPLC-MS and NMR showed that content of epinephrine present in the original sample remained unchanged compared to the control. There was no statistical difference in the UHPLC-MS and NMR signal amplitudes between the control and the expired samples. No chemical degradation byproducts were detected using NMR. There was no growth of any bacteria or fungus.Conclusion : Recurrent epinephrine shortages impact EMS and hospital operations in the United States. Individual administrators may be hesitant to authorize use of expired pharmaceuticals due to perceived potential complications or fear of litigation. This study shows that the original parenteral epinephrine remains sterile and detectably pure more than 2.5 years after expiration. Further study of the sterility and chemical integrity of expired medications that had been subjected to the conditions of EMS vehicles may be a future research endeavor based on the aforementioned paradigm.